Agrinfo using drones to support agribusiness development in Tanzania - Funja, Rose (Technical Centre for Agricultural and Rural Cooperation, 2018)
Rose Funja, Managing Director of Agrinfo Company Ltd (Tanzania), shares how the company grew since her participation in CTA s AgriHack Championship in 2013.